Profil Kesehatan Dasar Lansia Melalui Pemeriksaan Tekanan Darah Dalam Rangka Peringatan Hari Lanjut Usia Nasional di BKKKS Jatim - Rustam, Muh Zul Azhri; Susanti, Ari; Amalia, Nuke; Riestyowati, Maya Ayu (STIKES Yayasan RS.Dr.Soetomo, 2022)
Elderly is someone who has reached the age of 60 years and over. The older you get, the greater the risk for experiencing health problems, because of the degenerative process. The most common degenerative disease that affects the elderly is hypertension. The purpose of this study was to determine the basic health profile of the elderly through blood pressure checks in commemoration of the National Elderly Day in East Java Social Welfare Activities Coordinating Board (BKKKS). Methods This research was conducted in three stages, namely preparation, implementation and evaluation using an accidental sampling of 125 elderly participants. The results Most of the elderly participants had normal blood pressure as much as 51.20% compared to those with hypertension as much as 48.8%, because before doing the blood pressure check, they had physical activities such as morning exercise together. Most of the elderly have normal blood pressure